Measuring the reliability of knowledge management : instrument development and validation - Hesamamiri, Roozbeh (2013)
Aims to develop a measurement instrument that involves the five reliability dimensions of preoccupations with failure, reluctance to simplify interpretations, sensitivity to operations, commitment to resilence, and deference to expertise.